Direct Writing Target Structures by Two-Photon Polymerization. (1st September 2016) - Jiang, L. J.; Campbell, J. H.; Lu, Y. F.; Bernat, T.; Petta, N.
Abstract: Two-photon polymerization (2PP) offers an attractive option for direct writing micron- to millimeter-sized laser target components that support high-energy-density plasma physics research. 2PP was used to deterministically print a number of common targetlike structures including tubes, spatially periodic Rayleigh-Taylor–like surfaces, and low-density foams. The structures were printed using commercially available acrylic photoresins. The elemental compositions are reported for comparison with other polymers used for making target components. A number of foamlike structures ranging in size from tens to hundreds of microns and varying in density from 600 to 60 mg/cm 3 were readily printed in times ranging from several seconds to a few hours depending on the size. In addition, direct printing was demonstrated to fabricate graded-density foam comprising 12 individual layers with a vertical density gradient of 600 to 80 mg/cm 3 . Control of shrinkage and deformation during development and subsequent drying remains a challenge for certain structures and a focus of ongoing research.